MicroRNAs orchestrating senescence of endothelial and vascular smooth muscle cells. (September 2019) - Colpani, Ornella; Spinetti, Gaia
Abstract : During organism aging, the process of cellular senescence is triggered by critical stressors such as DNA damage, oncogenes, oxidative stress, and telomere erosion, and vascular cells are not exempted. Senescent cells stop proliferating but remain metabolically active producing pro-inflammatory signals in the environment collectively named senescence-associated secretory phenotype (SASP) that contribute to the amplification of the response to the neighbor and distant cells. Although the shift toward senescence is protective against tumors and needed during wound healing, the accumulation of senescent cells during aging due to an impairment of the immune system deputed to their clearance, can predispose to diseases of the cardiovascular system such as atherosclerosis. In this short review, we describe the main features of senescence of endothelial and smooth muscle cells and focus on the role non-coding RNAs of the microRNAs class in controlling this process. Finally, we discuss the potential of new strategies based on senescence removal in counteracting vascular disease burden.